2010
DOI: 10.1603/me09192
|View full text |Cite
|
Sign up to set email alerts
|

Detection of <I>Francisella tularensis</I> in Alaskan Mosquitoes (Diptera: Culicidae) and Assessment of a Laboratory Model for Transmission

Abstract: Tularemia is a zoonotic disease caused by the Category A bioterrorism agent Francisella tularensis. In Scandinavia, tularemia transmission by mosquitoes has been widely cited in the literature. We tested >2,500 mosquitoes captured in Alaska and found Francisella DNA in 30% of pooled samples. To examine the potential for transmission of Francisella by mosquitoes, we developed a mosquito model of Francisella infection. Larvae of Anopheles gambiae Giles and Aedes aegypti (L.) readily ingest F. tularensis but do n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 27 publications
2
23
0
Order By: Relevance
“…Neither the study by Thelaus et al or Triebenbach et al could show transmission of the bacteria from infected mosquitoes to uninfected mammal hosts. They also agree that there is no evidence for active replication of the bacterium within the mosquitoes [68,69]. There have been relatively few studies investigating the prevalence of F. tularensis in mosquitoes (Table 4).…”
Section: Mosquitoesmentioning
confidence: 86%
See 2 more Smart Citations
“…Neither the study by Thelaus et al or Triebenbach et al could show transmission of the bacteria from infected mosquitoes to uninfected mammal hosts. They also agree that there is no evidence for active replication of the bacterium within the mosquitoes [68,69]. There have been relatively few studies investigating the prevalence of F. tularensis in mosquitoes (Table 4).…”
Section: Mosquitoesmentioning
confidence: 86%
“…When uninfected mosquitoes fed on infected mice they were able to acquire the bacteria. In contrast, laboratory experiments by Triebenbach et al [69], infecting larvae from A. aegypti and Anopheles gambiae with F. tularensis subsp. novicida concluded that there was no evidence of transstadial transmission, that mosquitoes were unable to acquire the bacteria during a blood meal and that infected mosquitoes were not able to transmit the bacteria during a blood meal.…”
Section: Mosquitoesmentioning
confidence: 88%
See 1 more Smart Citation
“…In particular, tularemia cases in Europe are mainly concentrated in Germany, Sweden, British Columbia, Norway and France 4,20,21 . Other cases are reported in Japan, Alaska, Sudan and Turkey [22][23][24] . Currently, outbreaks caused by F. tularensis are generally rare and sporadic as the spread and incidence of the disease has been steadily decreasing 25 .…”
Section: Introductionmentioning
confidence: 98%
“…F. tularensis infects a wide range of hosts, which includes humans, but predominately infects small mammals such as rabbits, voles, and squirrels (24). F. tularensis has been isolated from arthropod vectors such as ticks (29,34), mosquitoes (28,43), and deerflies (24), which are also a source of transmission to humans (5,6). Additional modes of transmission to humans include contact with infected animals (30,31,36), ingestion of contaminated food or water (23,25), and inhalation of aerosolized bacteria (37,42).…”
mentioning
confidence: 99%